Fungi grow - Gianferrari, Maria (Beach Lane Books, 2023)
"Fungi are all around us. They root and fruit and twist and twine. The mycelium roots spread below ground while the mushroom fruits pop above the earth. Some are edible, and some are poisonous. Some help keep forests communicate, others recycle decaying matter. But all across the world, fungi are growing. Discover when, how, where, and why in this poetic and illuminating nonfiction picture book"--